Pengajaran Keterampilan Berbahasa Inggris untuk Siswa Kelas I SD di SDN Salatiga 06 - Setiamunadi, Antonina Anggraini; Listyani, Listyani (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
Along with the start of the Industrial Revolution 4.0 era, English language skills as a communication language used internationally are becoming increasingly important. These skills need to be taught not only at the secondary school and college levels, but also at the basic education level. However, there are still many elementary school children in Indonesia who do not have the opportunity or do not have the motivation to learn English. This is what prompted us to implement PkM at SDN Salatiga 06. With 16 (sixteen) PBI, FBS, UKSW students, we were committed to implementing PkM in the form of teaching communication skills using English for Grade I elementary school students. The sixteen students who taught were required to make a lesson plan first before they carried out their teaching practice, and they also had to prepare all the necessary teaching aids under the guidance and supervision of the lecturers. Activities took place from February to June 2023. We conclude that English language teaching is very necessary at the basic education level in preparing the young generation as early as possible to face the global era.